Kształtowanie uczuć patriotycznych wśród uczniów z niepełnosprawnością intelektualną = Cultivating patriotic feelings among students with intellectual disabilities - Wrycz, Iwona; Cysewska, Beata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
School plays a significant role in shaping patriotic attitudes among children and young people with intellectual disabilities. From an early age, it teaches them to cultivate patriotic attitudes and patterns, to respect the national emblem, flag, and Polish language. The goals of patriotic education include: creating emotional bonds between children and their families and peers, recognizing the value and beauty of nature, preparing children for work and life in society, and above all, developing love and attachment to their homeland, its traditions, and culture.
Keywords: patriotyzm; uczeń z niepełnosprawnością intelektualną; metody aktywizujące i praktyczne w pracy z uczniem z niepełnosprawnością intelektualną; patriotism; student with intellectual disabilities; activating and practical methods in working with students with intellectual disabilities